Can adenosine A2A receptor antagonists be used to treat cognitive impairment, depression or excessive sleepiness in Parkinson's disease?. (November 2020) - Jenner, Peter; Mori, Akihisa; Kanda, Tomoyuki
Abstract: Treatment of non-motor symptoms of Parkinson's disease (PD) is a major unmet need. Targeting adenosine A2A receptors may address some of the neuropsychiatric components of non-motor symptoms – notably cognitive impairment, depression and excessive daytime sleepiness. A2A receptors are located primarily on the indirect gamma-aminobutyric acid (GABA)-ergic striatal output pathway but are also present to some extent in limbic areas of the brain, particularly the nucleus accumbens. Extensive studies show that adenosine antagonists are effective in reversing cognitive deficits in a range of experimental models related to the early executive and visuo-spatial deficits seen in PD. Similarly, A2A receptor antagonists can reverse depressive symptoms in experimental models of PD, including models with high predictive value of effect in humans, and to the same extent as classical antidepressants. Importantly, A2A antagonists are effective in models of the motivational symptoms of depression, which may relate to the apathetic/anhedonic expression of depression that can occur in PD. Adenosine and A2A receptors play a prominent role in regulating the sleep-wake cycle with arousal attributed to A2A receptor antagonism. In rodents, A2A receptor antagonists appear to induce arousal in the active part of the daily cycle only, and not during the inactive phase. This was suggested in small clinical studies in PD where A2A antagonism improved daytime sleepiness without impairing nocturnal sleep. In conclusion, A2A antagonists have potential to affect a range of neuropsychiatric components of PD; this clinical potential requires further investigation in humans. Highlights: Effective treatment of non-motor symptoms (NMS) is a key unmet need in Parkinson's disease. Adenosine A2A receptors modulate neuropsychiatric components of NMS. Preclinical studies suggest A2A receptor antagonists may be effective in treating some NMS.